Using Technical and Financial Review and AHP Method to Find the Best Method of the Chlorine-Based Disinfection - Ebrahim Aboutalebi Shakour; Hosein Jamshidi (علوم و مهندسی آب و فاضلاب, 2017)
In this paper, research on six chlorine-based methods, which is one of the most widely used and effective methods of disinfection, is carried out, the advantages and disadvantages and their comparisons have been investigated.Also provided by Excel, computational software, Which will detail the cost of disinfection in stages for up to five years.The goal is to reach the best of the economic and technical landscape Which is a concern of many consultants and operators.In order to achieve this, nine criteria must be valued, by collecting questionnaires and collecting 34 questionnaires from experts in water, water supply and disinfection systems,Obtain important decision criteriaAnd by way of comparison with the help of software AHP and Expert choice .In order of preference by electrolysis of sodium chloride (Multi-oxidant), bleach(Sodium hypochlorite as a disinfectant) and hypochlorinator (Calcium hypochlorite) as best practices from the six of the most effective methods that are chlorine-based disinfection methods achieved.